Mechanisms of cross resistance between cisplatin and bleomycin in saccharomyces cerevisiae - Burgos-Molina, Antonio Manuel; Gil-Carmona, Luisa; Ruiz-Gómez, Miguel José (My University, 2019)
Tumor cells can simultaneously acquire resistance against a diverse group of drugs. This phenomenon is called pleotropic resistance or multidrug resistance. This mechanism could explain the tumor resistance observed in chemotherapy treatments with multiple agents. The aim of this work is to study possible mechanisms of cross resistance between Cisplatin and Bleomycin in Saccharomyces cerevisiae.
Keywords: Bleomicina; Tumores; Cisplatin; Bleomycin; Mechanisms of cross resistance